Mechanisms of Activation and Subunit Release in Ca 2+ /Calmodulin-Dependent Protein Kinase II - Pullara, Filippo (2017)
Calcium/calmodulin-dependent protein kinase II is an enzyme involved in many different functions, including the so-called long-term potentiation, a mechanism that strengthens synapses in a persistent mode and is believed to be a basic cellular mechanism for memory formation. Here we study the conformational changes of the enzyme due to phosphorylation of some key residues that are believed to drive the transition from an inhibited to an active state; it is this active state the one associated with long-term potentiation. We found that the conformational changes could be explained in terms of three charged regions in the three main subdomains of the enzyme: the hub, linker, and kinase. The role of phosphorylation is to change the charge relation between them, turning on and off their interactions and switching between an attractive state (nonphosphorylated or inhibited) and a not attractive one (phosphorylated or active). We also show that phosphorylated subunits become less stable, and this could favor their release from the multimer, as has been already observed experimentally.